The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1167/iovs.17-22807
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Autotaxin-LPA Pathway in Dexamethasone-Induced Fibrotic Responses and Extracellular Matrix Production in Human Trabecular Meshwork Cells

Abstract: The results of this study, including the robust induction of ATX by Dex treatment, in association with fibrotic changes and ECM production in HTM cells, collectively suggest a potential role for ATX-LPA pathway in the regulation of aqueous humor outflow and IOP in glaucomatous eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 63 publications
2
41
1
Order By: Relevance
“…1B). In a previous study, we reported that ATX was upregulated in the AH as well as in the outflow pathway in SOAG patients and that it may be involved in the inflammatory changes in TM that cause elevated IOP 28 . Several previous studies have also shown that cytoskeletal changes induced by ECM deposition and fibrosis of HTM cells impair AH outflow through the TM, leading to IOP elevation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…1B). In a previous study, we reported that ATX was upregulated in the AH as well as in the outflow pathway in SOAG patients and that it may be involved in the inflammatory changes in TM that cause elevated IOP 28 . Several previous studies have also shown that cytoskeletal changes induced by ECM deposition and fibrosis of HTM cells impair AH outflow through the TM, leading to IOP elevation.…”
Section: Discussionmentioning
confidence: 94%
“…Measurement of AtX, AtX isoforms, and tGf-β1, 2 and 3 in the AH. The level of ATX in the AH was determined using a two-site immunoenzymatic assay with an ATX assay reagent equipped with a Tosoh AIA system (Tosoh, Tokyo, Japan) as described previously 27,28,54,55 . The TGF-β levels in the AH were measured using the Bio-Plex Pro TGF-β Assay (Bio-Rad, CA, USA) following the manufacturer's protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Dex treatment did not decrease ATX activity significantly in liver and kidney, which indicates that there is organspecific regulation. In fact, Dex was reported to increase ATX expression in human trabecular meshwork cells and to be associated with fibrotic changes in the eye (55).…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the average relative protein abundance over all dexamethasone-treated TM cell samples (glaucomatous and nonglaucomatous together) did not show a significant change in fibronectin protein expression. In contrast, Honjo et al, 46 Peng et al, 47 Filla et al, 48 Downloaded from iovs.arvojournals.org on 09/06/2020 and Zhou et al 49 reported that the protein expression of fibronectin was significantly increased after exposing human TM cells to dexamethasone. Additionally, Li et al 50 reported the fibronectin protein secretion to be significantly increased in four human TM cell strains but to be decreased in one human TM cell strain after exposure to dexamethasone (both after 1 and 4 weeks of exposure).…”
Section: Figurementioning
confidence: 95%